2009
DOI: 10.1007/s00340-009-3517-9
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-modes and fiber-anisotropy characterization using low-coherence interferometry

Abstract: An optical low-coherence interferometry technique has been used to simultaneously resolve the mode profile and to measure the intermodal dispersion of guided modes of a few-mode fiber. Measurements are performed using short samples of fiber (about 50 cm). There is no need for a complex mode-conversion technique to reach a high interference visibility. Four LP mode groups of the few-mode fiber are resolved. Experimental results and numerical simulations show that the ellipticity of the fiber core leads to a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The latter leads to a more robust and simple setup and is typically known as spatially and spectrally resolved imaging [12]. However, the reported main disadvantage is, that "the method fails in the general case of multiple modes having similar power levels" [14]. Moreover, it has been shown that even low HOM contents can influence the modal contents measured by and thus have to be taken into account [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter leads to a more robust and simple setup and is typically known as spatially and spectrally resolved imaging [12]. However, the reported main disadvantage is, that "the method fails in the general case of multiple modes having similar power levels" [14]. Moreover, it has been shown that even low HOM contents can influence the modal contents measured by and thus have to be taken into account [15].…”
Section: Introductionmentioning
confidence: 98%
“…Different experimental setups have been proposed. The reference arm can be a separate beam outside the fiber under test [13], [14] or it can be incorporated into the same fiber by using one guiding mode as reference for the others. The latter leads to a more robust and simple setup and is typically known as spatially and spectrally resolved imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…18,19,33) A Gaussian beam is launched at the input facet of the optical fiber. A robust radially polarized beam of high quality is obtained due to the unique dispersion properties of the transverse fiber modes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spatially spectrally resolved imaging (S 2 ) [2] and low-coherence interferometry [3] can provide a detailed view of the modal content excited in the fibre, but they are limited to passive fibre characterisation and require precise alignment. Furthermore, these techniques do not allow realtime measurements.…”
mentioning
confidence: 99%